AN ANALYSIS ON THE RELATIONSHIP BETWEEN DESTINATION IMAGE, SATISFACTION, AND ELECTRONIC WORD-OF-MOUTH OF DOMESTIC TRAVELERS TO SA DEC FLOWER VILLAGE - Huỳnh Quốc Tuấn (Tạp chí Khoa học Đại học Đà Lạt)
The study aims to analyze the relationship between destination image, satisfaction, and electronic word-of-mouth (EWOM) behavior of 215 domestic travelers. The author uses the method of analyzing and testing linear structural equation models (SEM). The study has conducted an evaluation of measurement and structural models. The results show that cognitive image directly affects affective image. Cognitive image and affective image directly impact tourist satisfaction and tourist satisfaction directly impacts electronic word-of-mouth behavior. In addition, this study also shows that cognitive image has an indirect effect on tourist satisfaction through affective image and affective image has indirect effects on electronic word-of-mouth behavior through tourist satisfaction.